COSMONYMS AND THEIR PLACE IN LINGUISTICS, THEIR RELATIONSHIP TO THE UZBEKI LANGUAGE AND CULTURE (TAMADDUN NURI JURNALI, 2025)
This article emphasizes that the names of celestial bodies, that is, cosmonyms, are an important linguistic unit in the field of onomastics of the Uzbek language, and its linguocultural characteristics are determined by their semantic structure and use in a cultural context.